Intelligent Speed Bump - Samion, Norhafiza; Nor Arzmi, Amirul Aiman; Mat Yusof, Muhammad Alif; Mat Nasir, Nurul Iffah Syazwani (Penerbit UTHM, 2020)
Accidents are one of the causes of adverse impact on traffic disruption. Today's traffic control solutions method, forcing heavy vehicles to slow down the speed of the vehicles but it made traffic disruption more badly than needed.